Changes of ecological wisdom of Sundanese People on conservation of wild animals: A case study in Upper Cisokan Watershed, West Java, Indonesia - SIDIK PERMANA; JOHAN ISKANDAR; PARIKESIT PARIKESIT; TEGUH HUSODO; ERRI N MEGANTARA; RUHYAT PARTASASMITA (Society for Indonesian Biodiversity, 2019)
Abstract. Permana S, Iskandar J, Parikesit, Husodo T, Megantara EN, Partasasmita R. 2019. Changes of ecological wisdom of Sundanese People on conservation of wild animals: A case study in Upper Cisokan Watershed, West Java, Indonesia. Biodiversitas 20: 1284-1293. In the past Sundanese rural people had a very close relationship with the environment. They utilize natural resources based on traditional ecological knowledge (TEK) and is strongly influenced by their perception of nature. This article elucidates the mythology of Sundanese rural people on wild animals and the changes of rural people perceptions and their behavior to wild animals in the rural ecosystem based on a case study in Bojong Salam and Sukaresmi villages, Rongga district, West Bandung, the upper Cisokan watershed, West Java. Method used in this study was qualitative, while some techniques, including observation, participant observation, and semi-structured interview were applied. The result of study showed that in the past Sundanese the rural people of Upper Cisokan watershed, West Bandung, West Java owned myths on some wild animals that is inherited from their ancestor through oral and using mother language. The influence of these myths on wild animals caused the rural people had prohibited to kill these animals and important role for traditional conservation. Nowadays, however, some myths on wild animals of rural people have not eroded or not recognized by young generations. Consequently, some taboos in hunting and catching animal based on myths on wild animals have tended not been applied to conserve wild animals traditionally. Therefore, to develop appropriate nature conservation, the biophysical, the socio-economic and cultural aspects must be holistically considered.